Avaliação da qualidade dos dados do sistema de informação do câncer do colo do útero, do município de Vitória, Espírito Santo, 2007 - Almeida, Márcia Valéria de Souza (2009)
This study has evaluated the Information System SISCOLO along the year 2007 in Vitoria. It has analyzed accessibility, opportunity and completeness as data quality evaluation criteria aiming at the recognition of the system potential for becoming an epidemiological tool, widening its current usage for accountancy and control of the cytopathological tests pay roll. It has been defined in two dimensions: (1) System Quality, composed by data quality components, accessibility, opportunity and completeness; (2) System Production, looking upon the components ratio of the cervical screening in women 25 to 59 years and women in this age group, lesion prevalence, lesion profile change, lesion chronology and sample adequateness. The data is from the SISCOLO data bank covering the period from January to December of 2007, supplied by the Municipal Coordination of Viva Mulher. For each dimension group analysis has been done using the Program SPSS, version 15.0. For the prevalence calculation and its respective 95% confidence interval the Stata program has been used. The SISCOLO is an accessible system, with the opportunity (time lapse between collection and result release) varying from 14 to 45 days. Attributes completeness were found excellent for ―has done preventive testing before‖ and for ―material adequateness‖; good for ―year of the last preventive‖; and bad for school history and all the attributes on the fields of anamnesis and inspection of the uterus colon (Cytopathological Test Formulary - uterus colon). The provision of cervical screening by the municipality reached a ratio of 0,25 test/female/year. Lesion prevalence presented the following distribution: 9,56 for ASCUS (IC95% 8,4-10,8); 11,58 for LIE BG (IC95% 10,3-12,9) and 2,07 for LIE AG (IC95% 1,5-2,7). The ratio between low and high degree lesions was of 4, 19 women, with an average age for precursory lesions showing up in younger women (29 to 38 years of age). Among the slides examined 1, 1% presented unsatisfactory adequateness.. The information presented point to the need of improvement in traceability and uterus colon cancer control in Vitoria. The possibility of the components accessibility, opportunity and completeness usage for SISCOLO data production quality, will contribute to make it a more improved tool not only for finances but also for epidemiological use.